2014
DOI: 10.1097/hmr.0b013e31829fca10
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the board’s strategy-setting role on board-management relations and hospital performance

Abstract: Active strategy-setting by a governing board may generally improve hospital performance. Diverse members of governing boards should be involved in strategy-setting for hospitals. However, high board-management collaboration quality may be compromised if managerial autonomy is too highly restricted. Consequently, hospitals should support board-management collaboration about empowered contrasting board roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…As such, the paper extends insights reported elsewhere (Büchner et al, 2014;Raes et al, 2013) about the need to extend UE research beyond the inner circle of TMTs and gives greater consideration to other steps in the chain linked to the internal organisational context (Nielsen, 2010). As suggested by Carpenter et al (2004) and confirmed by the findings here reported, future studies would need to account for the possible existence of an indirect relationship between TMT composition and performance outcomes.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…As such, the paper extends insights reported elsewhere (Büchner et al, 2014;Raes et al, 2013) about the need to extend UE research beyond the inner circle of TMTs and gives greater consideration to other steps in the chain linked to the internal organisational context (Nielsen, 2010). As suggested by Carpenter et al (2004) and confirmed by the findings here reported, future studies would need to account for the possible existence of an indirect relationship between TMT composition and performance outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…Confidence in this finding is also reinforced by the multiple outcome measures used -going beyond the approach taken in many previous studies (Büchner et al, 2014) -to focus on performance from the patient, manager and staff perspectives. What transpires from the findings is that the cognitive, symbolic and communicative consequences of TMT heterogeneity, as theorised by Milliken & Martins (1996), have a positive impact on the overall performance of hospitals and, more in general, organisations.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations